Valoración de la proximidad a las Zonas Verdes Urbanas de la ciudad de Zaragoza como estrategia de adaptación a situaciones pandémicas - Natalia Bolea Tolón; Raúl Postigo Vidal; Carlos López Escolano (Ciudades, 2022)
The COVID-19pandemichas generated a change in the urban paradigm, leaving evidence of the need to plan and redesign cities under the concepts of "caring city" and "healthy city", in order to adapt and make them resilient to the new post pandemic reality. To support this idea, this document studies –by means of a questionnaire–the assessment that the citizens of the city of Zaragoza make of their urban green areas before, during and after confinement, as key public spaces for the development of urban life and support in the planning processes of the "healthy city" by allowing the maintenance of the minimum social distance of safety and promoting the health and physicaland mental well-being of the population